Data on measurement of the strain partitioning in a multiphase Zn-Al eutectic alloy - Zhicheng Wu; Stefanie Sandlöbes; Jing Rao; James S.K.L. Gibson; Benjamin Berkels; Sandra Korte-Kerzel (Data in Brief, 2018)
This paper presents original data related to the research article “Local mechanical properties and plasticity mechanisms in a Zn-Al eutectic alloy” (Wu et al., 2018). The raw data provided here was used for in-situ digital image correlation on the microstructural level using a new method described in the related study. The data includes sample preparation details, image acquisition and data processing. The described approach provides an approach to quantify the local strain distribution and strain partitioning in multiphase microstructures.